2010
DOI: 10.1186/1471-2474-11-57
|View full text |Cite
|
Sign up to set email alerts
|

Rotational alignment of the tibial component in total knee arthroplasty is better at the medial third of tibial tuberosity than at the medial border

Abstract: BackgroundCorrect rotational alignment of the femoral and tibial component is an important factor for successful TKA. The transepicondylar axis is widely accepted as a reference for the femoral component. There is not a standard reference for the tibial component. CT scans were used in this study to measure which of 2 tibial landmarks most reliably reproduces a correct femoro-tibial rotational alignment in TKA.Methods80 patients received a cemented, unconstrained, cruciate-retaining TKA with a rotating platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
102
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 25 publications
6
102
1
Order By: Relevance
“…However, multiple recent publications demonstrate that internal tibial component rotation still occurs and is a source of failure in TKA [3,6,17,18]. Correct rotation can be achieved using symmetric or asymmetric components, but the extent of coverage (especially posteromedial) may vary depending on component design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, multiple recent publications demonstrate that internal tibial component rotation still occurs and is a source of failure in TKA [3,6,17,18]. Correct rotation can be achieved using symmetric or asymmetric components, but the extent of coverage (especially posteromedial) may vary depending on component design.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 15% to 19% of patients undergoing TKA are not completely satisfied with the function of their joint [4,17,19,20]. We believe inadvertent internal rotation of the tibial tray, in an effort to increase tibial bone coverage, may be part of this problem and thus sought to evaluate the influence of component design (symmetric versus asymmetric components) on rotation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 While the transepicondylar axis is universally recognized as a primary reference for the femoral rotational alignment. 911 there is no consensus for the tibial rotational alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies related a poor functional outcome to femoral and tibial components rota tional malalignment. 13 Rotational malalignment may lead to patellar maltracking, anterior knee pain, flexion instability and premature wear of the polyethylene inlay. The rotational alignment of the femoral component has been extensively studied and useful reference axes for setting proper femoral rotation have been established, including the posterior con dylar axis, the midtrochlear line (Whiteside's line) and the transepicondylar axis.…”
Section: Introductionmentioning
confidence: 99%